Analysis In Economic Law On The Consumer Lifestyle Of The Young Generation Who Failed To Pay Paylater - Banjarnahor, David; Banjarnahor, Daulat Nathanael (Jurnal Mamangan, 2023)
Currently, the phenomenon of using Paylater services in Indonesia, especially among the younger generation, has become a major highlight in recent months, although it offers convenience, there are significant risks, especially the occurrence of "default", the impact of which can affect the stability of the economy, banking, and social society. The high number of defaults will disrupt economic stability, one of which is a decrease in purchasing power, in addition to the risk of inflation due to fines and interest on debt that are increasing and accumulating, creating a negative economic growth cycle. This banking sector situation is a serious challenge, with increasing non-performing loans so that they have bad credit status, it will thwart financial performance in business growth and investment, not to mention the additional operational costs to use the services of other parties in collection so that profitability decreases as well as public trust. Broadly speaking, if preventive measures are not taken, the younger generation who are caught in the default phase will experience financial decline, as a result they will experience emotional and mental stress so that negative social stigma will stick and ultimately will affect the creation of widespread and prolonged social injustice due to uncontrolled consumer behavior.